Mutations in ELAC2 associated with hypertrophic cardiomyopathy impair mitochondrial tRNA 3′‐end processing. Issue 10 (18th June 2019) - Saoura, Makenzie; Powell, Christopher A.; Kopajtich, Robert; Alahmad, Ahmad; AL‐Balool, Haya H.; Albash, Buthaina; Alfadhel, Majid; Alston, Charlotte L.; Bertini, Enrico; Bonnen, Penelope E.; Bratkovic, Drago; Carrozzo, Rosalba; et al.
Abstract: Mutations in either the mitochondrial or nuclear genomes are associated with a diverse group of human disorders characterized by impaired mitochondrial respiration. Within this group, an increasing number of mutations have been identified in nuclear genes involved in mitochondrial RNA metabolism, including ELAC2 . The ELAC2 gene codes for the mitochondrial RNase Z, responsible for endonucleolytic cleavage of the 3′ ends of mitochondrial pre‐tRNAs. Here, we report the identification of 16 novel ELAC2 variants in individuals presenting with mitochondrial respiratory chain deficiency, hypertrophic cardiomyopathy (HCM), and lactic acidosis. We provide evidence for the pathogenicity of the novel missense variants by studying the RNase Z activity in an in vitro system. We also modeled the residues affected by a missense mutation in solved RNase Z structures, providing insight into enzyme structure and function. Finally, we show that primary fibroblasts from the affected individuals have elevated levels of unprocessed mitochondrial RNA precursors. Our study thus broadly confirms the correlation of ELAC2 variants with severe infantile‐onset forms of HCM and mitochondrial respiratory chain dysfunction. One rare missense variant associated with the occurrence of prostate cancer (p.Arg781His) impairs the mitochondrial RNase Z activity of ELAC2, suggesting a functional link between tumorigenesis and mitochondrial RNA metabolism